Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s11136-017-1616-3
|View full text |Cite
|
Sign up to set email alerts
|

Moving from significance to real-world meaning: methods for interpreting change in clinical outcome assessment scores

Abstract: By careful planning of anchor selection, study design, and psychometric methods, COA researchers can establish defensible responder thresholds that ultimately aid patients and clinicians in making informed treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 11 publications
1
106
0
Order By: Relevance
“…Finally, the optimal scoring threshold was determined to identify patients whose AD would be considered "not in control." This study also validated the ADCT against a patientreported global assessment (i.e., PGA) of disease control, likely producing the most accurate and relevant data for establishing the validity of a new PRO because it is based on the patients' own experiences of the symptoms and/or functioning limitations 33 . In addition, a PGA of disease severity was used to measure patients' overall impression of their current AD severity.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, the optimal scoring threshold was determined to identify patients whose AD would be considered "not in control." This study also validated the ADCT against a patientreported global assessment (i.e., PGA) of disease control, likely producing the most accurate and relevant data for establishing the validity of a new PRO because it is based on the patients' own experiences of the symptoms and/or functioning limitations 33 . In addition, a PGA of disease severity was used to measure patients' overall impression of their current AD severity.…”
Section: Discussionmentioning
confidence: 88%
“…It has been suggested that the MID be used to identify ''responders'' to treatment. 21 For example, the U.S. Food and Drug Administration guidance document recommended identifying responders using empirical evidence from anchor-based methods and suggested that the ''difference in the PRO score for persons who rate their condition the same and better or worse can be used to define responders to treatment.'' 22 But using group-level change to identify responders would lead to misclassification of patients as responders when they have not actually changed.…”
Section: Methodsmentioning
confidence: 99%
“…Anchor-based method is a traditional and widely used method, which can verify the signi cance of changes through external indicators based on patients' subjective feelings [29]. However, it also has many problems, such as determination of suitable anchor, calculation of the difference between positive and negative values, selection of mean and median according to scores distributions, the appropriateness of using clinical objective indicators as objective anchors, and so on [30,31].…”
Section: Socio-demographic Characteristics Of the Samplementioning
confidence: 99%